FATORES DE RISCOS PARA DOENÇAS CARDIOVASCULARES EM DOCENTES DE ENSINO SUPERIOR: REVISÃO DE LITERATURA - Thayana Aparecida Nogueira Silva; Lanna Jéssica de Aquino; Viviane Lemos Silva Fernandes; Henrique Polleti Zani; Paulo Roberto Barbosa Evora; Daniella Alves Vento (UniEVANGÉLICA, 2016)
Objective: To discuss the risk factors prevalence of Cardiovascular Diseases in teachers. Data source: Was realized the bibliographic review in pubmed , scielo and bireme to identify publications addressing a thematic proposal. This study was conducted between August - December 2015 and were selected publications dating from 2000 using the key words "cardiovascular risk factors", "cardiovascular diseases" and "teachers". Data synthesis: It was observed that stress, physical inactivity and obesity associated with excessive workload of work, poor diet plays an important role in the growth of cardiovascular disease among teachers. Conclusion: It is clear that there are significant relationship between risk factors and cardiovascular disease among teachers which may compromise the individual's quality of life. But although there are many studies addressing factors of cardiovascular risk in workers , there is a lack of studies that address these risk factors in teachers, arousing greater interest to hold future a field study for scientific contribution. It is also expected to motivate other researchers to look for evidence and generate solutions to prevent or minimize such risk factors improving the quality of life of this professional.